INTEGRAÇÃO DE DADOS ESPACIAIS DE ASSENTAMENTOS DE REFORMA AGRÁRIA A UM BANCO DE DADOS GEOGRÁFICOS E DISPONIBILIZAÇÃO NA INTERNET UTILIZANDO OS SOFTWARES SPRING E SPRING WEB - Aguiar, Marcelo Cabral de; Gomes, Marisa Prado; Lima, Samuel do Carmo (Caminhos de Geografia, 2003)
This paper treats the characterization of an application of GIS aiming to help the land reform. It was used the software SPRING for generate cadastral maps of properties rural, on Minas Gerais State linked on a geographic database. The results of the work presented shows the potential application of techniques of GIS for the land reform in describing spatial information and individual parcels, as well as the fact that these maps are georeferenced.